The joint distribution of wealth and income risk: Evidence from Bern - Matthias Krapf (University of Basel, Center of Business and Economics (WWZ), 2018)
Using detailed tax data from the Swiss canton of Bern, I examine how changes in wealth are related to income risk. I find that only among elderly individuals high kurtosis of income risk may be positively correlated with wealth accumulation. Additionally, I document that a substantial share of taxpayers have negative net wealth. While wealth and income are positively correlated for positive net wealth taxpayers, this correlation is negative for negative net wealth taxpayers. These negative net wealth investors experience sharp increases in wealth and income in subsequent periods. Finally, wealth risk is more dispersed than income risk.
Keywords: 330